Delay and energy minimization for MEC-based secure communication - Pinyi REN; Qian XU (Tongxin xuebao)
Considering a physical-layer-security-aided confidential document transmission problem,a secure transmission strategy was proposed where the base station equipped with a mobile edge computing (MEC) server served as a relay to help compress,forward,and decompress.First,the Poisson point process was used to calculate the secure transmission probability for the scenario with multiple potential eavesdroppers.Then,a delay and energy minimization problem was formulated under a constraint on the two-hop secure transmission probability.The optimal compression and decompression scheme was obtained using the one-dimensional search combined with linear programming.Simulation results show that the document compression is necessary for the link with small achievable secrecy rate under a given secure transmission probability; otherwise,the document should be directly transmitted without compression.